1999
DOI: 10.1359/jbmr.1999.14.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Surface Expression of the STRO-1 and Alkaline Phosphatase Antigens on Discrete Developmental Stages in Primary Cultures of Human Bone Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
225
1
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(245 citation statements)
references
References 54 publications
14
225
1
5
Order By: Relevance
“…In culture, cells expressing Stro-1 À /ALP + accounted for approximately 40% of the population and Stro-1 + /ALP + a further 10%. These values are consistent with early passage cultured cells derived from known MSC sources: trabecular bone explants [17], bone marrow, synovial lining, adipose tissue, muscle, and a single passage of periosteum [35]. More surprising than the osteogenic phenotype of cultured HPDCs in this study was the presence of a consistent and stable Stro-1 + population.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In culture, cells expressing Stro-1 À /ALP + accounted for approximately 40% of the population and Stro-1 + /ALP + a further 10%. These values are consistent with early passage cultured cells derived from known MSC sources: trabecular bone explants [17], bone marrow, synovial lining, adipose tissue, muscle, and a single passage of periosteum [35]. More surprising than the osteogenic phenotype of cultured HPDCs in this study was the presence of a consistent and stable Stro-1 + population.…”
Section: Discussionsupporting
confidence: 85%
“…Initial cell isolates consistently contained large populations of CD34 + hematopoietic cells and ALP + osteogenic cell types, small numbers of smooth muscle, endothelial and adipocytic cells, and small subpopulations of Stro-1 + cell types. Based on the study of developmental phenotypes of stromal cell cultures, it has been suggested that Stro-1 + /ALP À cells represent a less differentiated osteoblastic phenotype, Stro-1 + /ALP + cells an intermediate stage, and Stro-1 À /ALP + cells the most mature [17]. These findings build on work by Lim [24], who identified potential precursor populations within periosteal cultures.…”
Section: Discussionmentioning
confidence: 72%
“…After 4 weeks of induction, cultures were either stained with Alizarin red solution or analyzed for levels of extracellular calcium deposits (5 Â 10 3 MSC per well in 96-well plates, quadruplicate cultures) in the presence of o-cresol-phthalein-complexon (Sigma) with an absorbance read at 570 nm as previously described [5,26]. Adipogenesis was induced as previously described [5].…”
Section: In Vitro Differentiation Assaysmentioning
confidence: 99%
“…Human mesenchymal stem cells (MSC), which are first isolated from bone marrow (BM) [1,2] and subsequently isolated from other tissues such as adipose tissue, cutaneous tissue, fetal hepatic and pulmonary tissue [3][4][5][6][7][8][9][10][11], are pluripotent progenitors for a variety of tissues including bone, cartilage, tendon, fat, and muscle [12]. It has been approved have the capability to support expansion of hematopoietic stem cells (HSC) through expressing cytokines and reconstructing hematopoietic microenvironment [13,14].…”
Section: Introductionmentioning
confidence: 99%